Integrating Ayurveda into Addiction Medicine: A Pilot Trial of Ksheerbala Taila Nasya for Nicotine De-Addiction (International Journal of Ayurveda and Pharma Research, 2025)
Commonly found in tobacco derivatives, nicotine is one of the most common forms of addiction in today’s world. With growing dependency on nicotine irrespective of gender or standard of living humans are exposed towards basic to most fatal diseases. According to WHO- global health report, one-fourth (24.9%) of the population including both sexes are nicotine dependent, 40.3% men and 9.5% women. Although there have been many attempts on nicotine de-addiction trials most have failed or relapsed. In this study 10 nicotine dependent individuals were randomly selected from OPD. They were given Nasya therapy with Ksheerbala oil (10 drops each nostril) followed by Tikshna Snaihika Dhumapana after Mukha Abhyanga with Tila taila and Vastra Swedana for a period of 7 days in indoor department with Pratimarsha Nasya (2 drops each nostril) of same oil in the next 7 days. All the 10 cases showed marked decrease in nicotine dependence with highly significant p-value of 0.0019. Nicotine being highly addictive is an anxiolytic drug affecting synaptic junctions of central nervous system. Nasya one of the five Karmas of Panchakarma, is a simple procedure that can be done on OPD basis giving admirable results in de-addiction.